Pre-pregnancy body mass index and offspring neurobehavioral development: a birth cohort study - Sun, Peng; Hu, Youdan; Wei, Min; Li, Xiuxiu; Wu, Zhiling; Liu, Xuemei; Guo, Zhaoyi; Li, Wei; Chen, Wei-Qing; Zhong, Shuya (Frontiers in Nutrition, 2025)
BackgroundNeurodevelopmental disorders in children, due to their high prevalence and potential long-term adverse outcomes, require early identification and intervention. Prenatal environmental factors may affect offspring neurodevelopmental trajectories, but supporting evidence is limited. This study aims to examine the longitudinal association between maternal pre-pregnancy BMI and offspring neurobehavioral development.MethodsBased on the Shenzhen Birth Cohort established in 2018, 2,255 mother–child pairs were included. Maternal sociodemographic characteristics and pre-pregnancy BMI were obtained through prenatal questionnaires. Child neurobehavioral development from 1 to 36 months of age was assessed using the Ages and Stages Questionnaires, Third Edition (ASQ-3). Generalized estimating equations were used to analyze the association between pre-pregnancy BMI and offspring neurobehavioral development.ResultsPre-pregnancy BMI was categorized into underweight (16.1%), normal (74.9%), and overweight/obesity (9.0%). After adjusting for confounders, maternal overweight/obesity significantly increased the risk of developmental delays in the communication (aOR = 1.55, 95% CI: 1.25–1.92) and problem-solving domains (aOR = 1.44, 95% CI: 1.14–1.83). Sex-stratified analysis showed that this association was significant only in boys for the problem-solving (aOR = 1.60, 95% CI: 1.20–2.13) and personal-social domains (aOR = 1.43, 95% CI: 1.10–1.86) (p < 0.01).ConclusionMaternal pre-pregnancy overweight/obesity was an independent risk factor for offspring neurobehavioral developmental delays, with sex-specific effects. These findings suggested that pre-pregnancy weight management should be included in primary prevention strategies for neurodevelopmental disorders.